2020
DOI: 10.1126/sciadv.aba3274
|View full text |Cite
|
Sign up to set email alerts
|

Same father, same face: Deep learning reveals selection for signaling kinship in a wild primate

Abstract: Many animals rely on facial traits to recognize their kin; however, whether these traits have been selected specifically for this function remains unknown. Using deep learning for face recognition, we present the first evidence that interindividual facial resemblance has been selected to signal paternal kinship. Mandrills (Mandrillus sphinx) live in matrilineal societies, in which females spend their entire lives not only with maternal half-sisters (MHS) but also with paternal half-sisters (PHS). We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 46 publications
2
58
0
Order By: Relevance
“…However, evidence is mounting that unfamiliar kin are capable of recognizing each other through phenotypic matching (Mateo, 2004; Widdig, 2007). Several studies have reported auditory, visual and olfactory cues that contain information about relatedness (Bower, Suomi, & Paukner, 2012; Charpentier, Boulet, & Drea, 2008; Charpentier et al., 2020; Deecke, Barrett‐Lennard, Spong, & Ford, 2010; Huchard et al., 2010; Kazem & Widdig, 2013; Levréro et al., 2015; Mateo, 2002, 2017; Setchell et al., 2011) and animals respond differently to such cues from related versus unrelated individuals (Charpentier, Crawford, Boulet, & Drea, 2010; Charpentier et al., 2017; Gilad, Swaisgood, Owen, & Zhou, 2016; Henkel & Setchell, 2018; Kessler, Scheumann, Nash, & Zimmermann, 2012; Leclaire, Nielsen, Thavarajah, Manser, & Clutton‐Brock, 2013; Levréro et al., 2015; Pfefferle, Kazem, Brockhausen, Ruiz‐Lambides, & Widdig, 2014; Pfefferle Ruiz‐Lambides, & Widdig, 2014, 2015). Many of these studies have focused on species closely related to Assamese macaques, so it is plausible that the males in our study are capable of recognizing unfamiliar kin through similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence is mounting that unfamiliar kin are capable of recognizing each other through phenotypic matching (Mateo, 2004; Widdig, 2007). Several studies have reported auditory, visual and olfactory cues that contain information about relatedness (Bower, Suomi, & Paukner, 2012; Charpentier, Boulet, & Drea, 2008; Charpentier et al., 2020; Deecke, Barrett‐Lennard, Spong, & Ford, 2010; Huchard et al., 2010; Kazem & Widdig, 2013; Levréro et al., 2015; Mateo, 2002, 2017; Setchell et al., 2011) and animals respond differently to such cues from related versus unrelated individuals (Charpentier, Crawford, Boulet, & Drea, 2010; Charpentier et al., 2017; Gilad, Swaisgood, Owen, & Zhou, 2016; Henkel & Setchell, 2018; Kessler, Scheumann, Nash, & Zimmermann, 2012; Leclaire, Nielsen, Thavarajah, Manser, & Clutton‐Brock, 2013; Levréro et al., 2015; Pfefferle, Kazem, Brockhausen, Ruiz‐Lambides, & Widdig, 2014; Pfefferle Ruiz‐Lambides, & Widdig, 2014, 2015). Many of these studies have focused on species closely related to Assamese macaques, so it is plausible that the males in our study are capable of recognizing unfamiliar kin through similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[ 69 ] Note, however, that they treat infected paternal half‐siblings exactly as they treat infected distant kin or nonkin, even though paternal half‐siblings are every bit as related to them as are maternal ones, and can be recognized as kin. [ 70 ] Yet of course maternal half‐siblings are exposed to one another a great deal because they are raised together from birth, whilst paternal half‐siblings grow up in entirely different families. [ 70 ] I suggest, then, that mandrills’ disregard of contagion when attending to maternal kin might reflect not their genetic relationship, but their larger familiarity with them and hence with their parasites.…”
Section: It's a Small Worldmentioning
confidence: 99%
“…[ 70 ] Yet of course maternal half‐siblings are exposed to one another a great deal because they are raised together from birth, whilst paternal half‐siblings grow up in entirely different families. [ 70 ] I suggest, then, that mandrills’ disregard of contagion when attending to maternal kin might reflect not their genetic relationship, but their larger familiarity with them and hence with their parasites.…”
Section: It's a Small Worldmentioning
confidence: 99%
“…Severe male aggression towards females occurs but appears relatively infrequent for human observers. Female relatives form tight social relationships [33], including aggressive coalitions against males that can lead to male's death (in captivity: [37]).…”
Section: Introductionmentioning
confidence: 99%